Atrial fibrillation self screening, management and guideline recommended therapy (AF SELF SMART): A protocol for atrial fibrillation self-screening in general practice - Katrina Giskes; Nicole Lowres; Jialin Li; Jessica Orchard; Charlotte Hespe; Ben Freedman (International Journal of Cardiology: Heart & Vasculature, 2021)
Background: Opportunistic screening for silent atrial fibrillation (AF) is recommended to reduce stroke, but screening rates are sub-optimal in general practice. We hypothesize that patient self-screening in the waiting room may improve screening and detection of AF. Methods and analyses: This proof-of-concept study tests a purpose-designed AF self-screening station and customised software which seamlessly integrates with general practice electronic medical records and workflow. The self-screening station records a lead-1 ECG. The software automatically (1) identifies eligible patients (aged ≥65 years, no AF diagnosis) from the practice appointment diary; (2) sends eligible patients an automated SMS reminder prior to their appointment; (3) creates individualised QR code to scan at self-screening station; and (4) imports the ECG and result directly into the patients’ electronic medical record. Between 5 and 8 general practices in New South Wales, Australia, will participate with an aim of 1500 patients undertaking self-screening. The main outcome measures will be the proportion of eligible patients that undertook self-screening, incidence of newly-diagnosed AF, and patient and staff experience of the self-screening process. De-identified data will be collected using a clinical audit tool, and qualitative interviews will determine patient and staff acceptability. Ethics and dissemination: Ethics approval was received from the University of Sydney Human Research Ethics Committee in June 2019 (Project no: 2019/382) and the University of Notre Dame Human Research Ethics Committee (Project no: 019145S) in October 2019. Results will be disseminated through various forums, including peer-reviewed publication and conference presentations.Trial registration numberACTRN12620000233921.